Pengaruh Brand Image Terhadap Brand Loyalty Dengan Brand Trust Sebagai Variabel Intervening (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Angkatan 2020 Universitas Islam Malang Pengguna Produk Unilever Personal Care) - Utomo, Dimas Khrisna; Rachma, N.; Ramadhan, Tri Sugiarti (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study was conducted to determine the effect of Brand Image on Brand Loyalty mediated by the Brand Trust on Economics and Business students at the Islamic University of Malang in 2020 are users of Unilever personal care products. this research uses explanatory research and a quantitative approach. The data source of this research is primary data obtained from answers to statements when distributing questionnaires to respondents who meet the criteria. The sampling technique used is non probability sampling with purposive sampling technique. The number of samples in this study were 110 respondents obtained from the Malhotra formula. to solve the problem in this study using the outer model test and inner model test with the help of data analysis using SmartPLS 4.1.0.6. The results of this study are Brand Image have a direct effect on Brand Trust. Brand Image have a direct effect on Brand Loyalty. Brand Trust have a direct effect on Brand Loyalty. Brand Image have an indirect effect on Brand Loyalty mediated by Brand Trust. Keywords: Brand Image, Brand Trust, Brand Loyalty